Common Coupled Fixed Point Theorem for Geraghty-Type Contraction in Partially Ordered Metric Spaces. (18th March 2018) - Liu, Xiao-lan; Zhou, Mi; Damjanović, Boško
Abstract : We study the existence and uniqueness of common coupled fixed point of four self-mappings for Geraghty-type contraction using weakly compatible mappings in partially ordered metric spaces with common limit range property (denoted by( C L R S T ) ), the property ofE . A, and so on. It is noted that the continuity of mappings and completeness of spaces can be removed. Our results improve, extend, complement, and generalize several existing results in the literature. Also, some examples are provided to illustrate the usability of our results.